An assessment of the economic burden of senile chronic diseases in China based on China Health and Retirement Longitudinal Survey. (3rd May 2020) - Dong, Xiayan; Chen, Linhong; Xu, Zhiming; Xu, Xiaocang
ABSTRACT: Objective: This study assessed the economic burden of senile chronic diseases (SCD) in China. Methods: Based on China Health and Retirement Longitudinal Survey data, we used propensity score matching to compare the economic burden of SCD for families with and without members with SCD. Results: We examined three aspects of economic burden: health service utilization, including health care utilization and expenditure, family daily consumption spending, and workforce participation of family members in labor markets. SCD-families showed a higher hospitalization rate and number of outpatient visits than the control group. SCD-families also consumed less per capita. Additionally, the negative influence of SCD on total family income may be partially offset by increasing the labor force participation rate of healthy family members. Finally, we also discussed the burden of SCD  in different educational status. Conclusions: Relevant results may provide insight into formulating health and labor policies by the Chinese government. The study significance consists of the selection of matching variables and robustness, whereas study limitations include the omission of other important variables.